Entrepreneurship Management in Higher Education: Fostering Student Creativity and Independence at the University of Palangka Raya - Kusnida Indrajaya (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the effectiveness of entrepreneurship program management in fostering student creativity and independence through student cooperatives at the University of Palangka Raya. The research aims to analyze how program policies impact the development of entrepreneurial knowledge, skills, and job creation. A qualitative approach was used, involving observations, interviews with program participants, and documentation analysis from November 2024 to early 2025. Data were analyzed using interactive model techniques through reduction, presentation, and conclusion drawing. The findings show that student cooperatives serve as an effective entrepreneurial learning environment, enhancing students' creativity in product development, marketing strategies, and digital business ventures. While the program has successfully developed entrepreneurial competencies, challenges such as capital limitations and lack of risk-taking confidence remain. These results contribute to the understanding of student entrepreneurship development and offer insights for improving similar programs in higher education institutions.